1984
DOI: 10.1159/000183299
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Progressive (‘Crescentic’) Glomerulonephritis and Monoclonal Gammapathies

Abstract: In 3 patients rapidly progressive glomerulonephritis revealed plasma cell dyscrasia in 2 cases and Waldenstrom’s macroglobulinemia in the 3rd. Renal biopsy showed proliferative glomerulonephritis with marked endo- and extracapillary (crescentic) proliferation. In case 1, corticosteroids and cyclophosphamide favorably influenced the course of the disease. The 2nd patient was not treated and went on to maintenance hemodialysis. In the 3rd case, plasma exchange and cytotoxic drugs allowed discontinuation of hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…There were 11 men and three women aged 55 to 75 yr at the time of diagnosis of kidney disease (mean age 67.6 yr). Renal symptoms included a nephrotic syndrome in seven patients (4,5,6,7,8,12, and 13) associated with acute kidney injury in four cases (6, 7, 8, and 12). The average daily proteinuria in patients with the nephrotic syndrome was 7.2 g (4.5 to 16.0 g).…”
Section: Clinical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 11 men and three women aged 55 to 75 yr at the time of diagnosis of kidney disease (mean age 67.6 yr). Renal symptoms included a nephrotic syndrome in seven patients (4,5,6,7,8,12, and 13) associated with acute kidney injury in four cases (6, 7, 8, and 12). The average daily proteinuria in patients with the nephrotic syndrome was 7.2 g (4.5 to 16.0 g).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…At the time of renal disease diagnosis, the lymphoproliferative disorder consisted of WM in seven patients (1,2,3,7,8,9, and 11), small B cell non-Hodgkin lymphoma in two patients (4 and 12), multiple myeloma in one patient (patient 5), and B cell lymphoma of the splenic marginal zone in one patient (patient 10). Three patients (6, 13, and 14) had an "IgM-related disorder.…”
Section: Hematologic and Immunologic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which it can do this include nephrocalcinosis, renal stones, myeloma kidney, amyloidosis and the entity known as light chain nephropathy. It is clear that benign paraproteinaemias can also cause renal impairment if the light chains produced have specific features that make them directly toxic to the kidney [1,2]. The Pi of the immunoglobulin protein has been implicated in this nephrotoxic potential [3].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed an addi tional 18 patients with dysproteinemic states (excluding essential cryoglobulinemia) where a proliferative glom erulonephritis was however the predominant histological finding [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Ten had multiple myeloma [5][6][7][8][9]12,15,17,18], 6 had monoclonal gammapathy [10][11][12][13]17] and 2 had macroglobulinemia [14,18]. In 9 of these 18 cases [8,10-14, 17, 18], insufficient data were available to evaluate and further subclassify the glomerular lesions.…”
Section: Introductionmentioning
confidence: 99%